2022
DOI: 10.1002/jmv.28276
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal samples versus lesion specimens at diagnosis in patients infected with monkeypox virus in Northern France

Abstract: The ongoing outbreak of monkeypox virus (MPXV) is the largest one in historically non‐endemic countries. Early reports described atypical epidemiological and clinical presentations. We investigated MPXV DNA detection in oropharyngeal samples (OPS), and compared the viral load to that in lesion samples at diagnosis in patients infected with MPXV. We retrospectively included patients suspected to have monkeypox in Northern France, who underwent a MPXV PCR in the Virology Laboratory, University Hospital of Lille,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…detected viral DNA in 55 OPS out of 61, with a median Ct value of 29.2 (IQR: 24.4–33.9); since those patients had other typical lesions with higher viral load, they concluded that OPS in this population might not be very useful. 5 In our study, we found that OPS was positive for MPXV DNA in 69% (191/278) of the cases with a median Ct value of 29 (IQR: 25–33). Amongst MPX patients, although lesion swab resulted negative in 15 cases, the diagnosis was confirmed in 11 patients due to the presence of OPS alone or in combination with AS/PL samples while in 4 patients on AS alone.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…detected viral DNA in 55 OPS out of 61, with a median Ct value of 29.2 (IQR: 24.4–33.9); since those patients had other typical lesions with higher viral load, they concluded that OPS in this population might not be very useful. 5 In our study, we found that OPS was positive for MPXV DNA in 69% (191/278) of the cases with a median Ct value of 29 (IQR: 25–33). Amongst MPX patients, although lesion swab resulted negative in 15 cases, the diagnosis was confirmed in 11 patients due to the presence of OPS alone or in combination with AS/PL samples while in 4 patients on AS alone.…”
mentioning
confidence: 47%
“…compared oropharyngeal swab (OPS) and lesion sample (LS), concluding that OPS might not be useful for diagnosis. 5 …”
mentioning
confidence: 99%
“…The baseline characteristics of the 14 studies included in the systematic review and meta-analysis consisting of three case series ( Thornhill et al., 2022a ; Thornhill et al., 2022b ; Palich et al., 2023 ), two cross-sectional studies ( García-Piqueras et al., 2022 ; Ouafi et al., 2023 ), eight prospective observational studies ( Loconsole et al., 2022 ; Mailhe et al., 2022 ; Nörz et al., 2022 ; Peiró-Mestres et al., 2022 ; Tarín-Vicente et al., 2022 ; Ubals et al., 2022 ; Veintimilla et al., 2022 ; Silva et al., 2023 ), and one retrospective study ( Hasso et al., 2022 ) are explained in Table 1 . Most of the studies were conducted in mpox non-endemic countries such as Spain (5/14, 35.71%), France (3/14, 21.42%), Italy (1/14), Germany (1/14), Canada (1/14), and Brazil (1/14).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another in vivo study observed a remarkable correlation between viral DNA load and infectivity in the BSC-1 cell line with epithelial morphology. Moreover, an mpox-infected patient with lesions is considered infectious till the crust from the crusty lesions falls off ( Ouafi et al., 2023 ). Notably, this extremely envisages a higher risk of transmission of infection from dermal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It also advises collecting and testing additional specimens (such as blood, semen, urine, and genital and rectal swabs) [ 51 ]. However, oropharyngeal swabs (OPS) and lesion samples (LS) were evaluated by Ouafi et al, who concluded that OPS might not be helpful for diagnosis [ 52 ].…”
Section: Clinical and Laboratory Characteristics And Diagnosis Of Mon...mentioning
confidence: 99%